Hospital-Based Prevalence of Malaria and Dengue in Febrile Patients in Bangladesh - Faruque, Labib I. (The American Society of Tropical Medicine and Hygiene, 2012)
We conducted a nationwide study at six tertiary hospitals from December 2008 through November 2009 to investigate etiologies of febrile illnesses in Bangladesh. Febrile patients meeting a clinical case definition were enrolled from inpatient and outpatient medicine and pediatric units. We assessed 720 febrile patients over 12 months; 69 (9.6%) were positive for IgM antibodies against dengue virus by enzyme-linked immunosorbent assay, and four malaria patients (0.56%) were confirmed with immuno-chromatography and microscopic slide tests. We identified dengue cases throughout the year from rural (49%) and urban areas (51%). We followed-up 55 accessible dengue-infected patients two months after their initial enrollment: 45 (82%) patients had fully recovered, 9 (16%) reported ongoing jaundice, fever and/or joint pain, and one died. Dengue infection is widespread across Bangladesh, but malaria is sufficiently uncommon that it should not be assumed as the cause of fever without laboratory confirmation.